Heat release characteristics of a latent heat storage heat exchanger by scraping the solidified phase change material layer. (15th August 2020) - Maruoka, Nobuhiro; Tsutsumi, Taichi; Ito, Akihisa; Hayasaka, Miho; Nogami, Hiroshi
Abstract: Latent heat storage (LHS) is one of the key methods to level renewable energy and utilize waste heat. In this method, heat is stored as latent heat of the phase change material (PCM) during melting. Releasing the stored heat in PCM consumes considerable time because the heat release rate is slow when a solidification layer of PCM is formed on the heat transfer wall during the heat release period. The authors have proposed a new mechanism for rapid heat exchange in LHS, i.e., by scraping the solidified PCM layer on the heat transfer wall. In this mechanism, the heat transfer wall is a rotating cylindrical tube to which a fixed blade is attached. During the heat release period, PCM is solidified on the tube, and the solidified layer is immediately removed using the fixed blade. In this study, a laboratory-scale setup with 1 kg of sodium acetate tri-hydrate as PCM was developed, and the effect of rotation rate on the heat release rate was experimentally examined. The results showed that the heat release rate during rotation accelerated by more than 100 times compared with the rate without rotation, and it increased with the rotation rate of the cylindrical tube. Highlights: New concept for heat transfer accelalation in Latent heat storage (LHS) is proposed. In LHS, heat is stored as latent heat of phase change material (PCM). Solidified layer of PCM prevents the heat transfer furing heat release period. The heat release rate is inovatevely accelerated by the scraping the solidified PCM. The overall heat transfer coefficient in LHS reaches more than 2000 W/m 2 K.